Aplicación de los geosintéticos entre las veredas los Cardones y el Machín, para mejorar la vía terciaria, ubicada en el municipio de San Juan del Cesar (2022)
The following is the research entitled, application of geosynthetics between the Cardones and the Machin, to improve the tertiary road, located in the municipality of San Juan del Cesar. The objective is to build a state of knowledge on the different applications of geosynthetics applied in the construction of an unpaved road, in order to propose an efficient and economically viable alternative for the road section with a length of 17 kilometers. For this purpose, a qualitative and descriptive methodology was presented, using primary sources (observation in field work) and secondary sources (review of texts). The results identified the deterioration of the 17 kilometers in the study section, presenting gullies in the road due to the flow of water, due to the lack of drainage on steep slopes, which makes access to the villages difficult. As for geosynthetic alternatives applied to unpaved roads and rural roads, geotextiles, geogrids and geocells have improved their performance by taking care of natural resources and making the best use of granular materials. The alternative to the use of geosynthetics that solves the study area is the use of geotextile, since it has the function of draining and separating the granular layers, thus avoiding the loss of aggregates. It was concluded that the use of geotextile reduces the appearance of reflection cracks due to the poor distribution of stresses on the wearing course